Oznaczmy:
[tex]x=\sqrt[3]{9-4\sqrt{5} } + \sqrt[3]{9+4\sqrt{5} }[/tex]
[tex]a=\sqrt[3]{9-4\sqrt{5} }[/tex]
[tex]b= \sqrt[3]{9+4 \sqrt{5} }[/tex]
[tex]x=a+b[/tex]
--------------------------
[tex]a^3+b^3=\left(\sqrt[3]{9-4\sqrt{5} }\right) ^3+\left(\sqrt[3]{9+4 \sqrt{5} }\right) ^3=9-4\sqrt{5}+9+4\sqrt{5}=18[/tex]
[tex]ab=\sqrt[3]{9-4\sqrt{5} }\cdot \sqrt[3]{9+4\sqrt{5}}=\sqrt[3]{(9-4\sqrt{5})(9+4\sqrt{5})}=\sqrt[3]{81-80} =\sqrt[3]{1}=1[/tex]
--------------------------
[tex](a+b)^3=a^3+3a^2b+3ab^2+b^3=a^3+b^3+3ab(a+b)[/tex]
[tex](a+b)^3=18+3\cdot 1(a+b)[/tex]
[tex](a+b)^3=18+3(a+b)[/tex]
Podstawiamy:
[tex]x=a+b[/tex]
[tex]x^3=18+3x[/tex]
[tex]x^3-3x-18=0[/tex]
[tex]x^3-27-3x+9=0[/tex]
[tex](x - 3)(x^2 + 3x + 9)-3(x-3)=0[/tex]
[tex](x-3)(x^2+3x+9-3)=0[/tex]
[tex](x-3)(x^2+3x+6)=0[/tex]
[tex]x-3=0 \Rightarrow x=3[/tex]
lub
[tex]x^2+3x+6=0[/tex]
[tex]\Delta=3^2-4\cdot 1\cdot 6=9-24=-15<0[/tex]
============================
[tex]\sqrt[3]{9-4\sqrt{5} } + \sqrt[3]{9+4\sqrt{5} }=3[/tex]